Acute pancreatitis concomitant with diabetic ketoacidosis: a cohort from South China. Issue 3 (March 2020) - Yuan, Shiwen; Liao, Jinli; Cai, Ruibin; Xiong, Yan; Zhan, Hong; Zheng, Ziyu
Objective: To evaluate the clinical characteristics of acute pancreatitis (AP) concomitant with diabetic ketoacidosis (DKA) in a cohort from South China and identify factors associated with early detection of DKA in AP patients. Methods: Inpatient medical records of AP concomitant with DKA were retrospectively reviewed. Results: Forty-eight patients with AP concomitant with DKA were enrolled in this study. The results indicated that comorbidity history of diabetes mellitus and mental status of not alert on admission were factors associated with DKA in AP patients. Compared with patients without DKA, patients with DKA showed significantly higher rates of hypertriglyceridemia and lower rates of gallstones than those without DKA. AP patients with concurrent DKA had higher levels of serum triglycerides, longer lengths of hospital stays, and higher complication rates of systemic inflammatory response syndrome and acute kidney injury. Conclusion: AP patients might have higher risks of concomitant DKA if presenting as not alert upon admission or if they have past medical histories of diabetes mellitus. Serum triglyceride levels were significantly higher in AP patients with DKA. DKA raised the severity of AP, but did not increase in-hospital mortality.